Regional Expansion of Land Ownership Certificates at the Batu Bara National Land Agency Office - Irda Pratiwi; Emmi Rahmiwita Nasution; Muhammad Salim Fauzi Lubis; Arya Rahmadansyah; Juwita Juwita (Jurnal Ilmiah Advokasi, 2024)
Regional expansion in the Certificate of Ownership Rights is a concrete manifestation of Regional Autonomy. The process of regional expansion of the Certificate of Ownership Rights on land at the National Land Agency Representative Office of Batu Bara Regency is to make a letter of application for the process of regional expansion of the Certificate of Ownership Rights of land which is to be expanded at the Office of the National Land Agency Representative of Batu Bara Regency, then complete the documents. Requirements for the application for the expansion process of the Certificate of Ownership that want to be expanded at the National Land Agency Representative Office of Batu Bara Regency, after the application and requirements are complete, after that the Office of the National Land Agency Representative of Batu Bara Regency can process the application for regional expansion in the Certificate of Ownership Rights on the land applied for. The problem with the Certificate of Ownership Rights for land at the Batu Bara Regency Representative National Land Agency Office is that the position of the land is not in accordance with the existing application system at the Batu Bara Regency Representative National Land Agency Office, so that the Batu Bara Regency Representative National Land Agency Office experiences difficulties in expanding the Certificate of Ownership of land.Keywords: Expansion; Certificate of Ownership; Land.